DEVELOPMENT FOR DIABETES PATIENT CARE MODEL BY COMMUNITY PARTICIPATION CHAIYAPHUM PROVINCE - รอญยุทธ วนิดา; ระวิวรรณ นิกร; รัตนอาภรณ์ วไลพร (Primary Health Care Journal (Northeastern Edition), 2024)
This research and development used a mixed research design. The purpose of this mixed methods research was to develop a diabetes care model with community participation in Chaiyaphum Province. The study consisted of 3 phases: 1) studying the factors influencing self-care behavior of diabetes with patients in Chaiyaphum Province, 2) developing a diabetes care model with community participation in Chaiyaphum Province, and 3) investigating the effectiveness of the diabetes care model with community participation in Chaiyaphum Province. The research was conducted between January 2023 and May 2024. The instruments used for data collection were a questionnaire and focus group discussion. The statistics used for data analysis included descriptive statistics and inferential statistics, including stepwise multiple regression, t-test, analysis of covariance, and content analysis. The results of this study were as follows: 1) The factors influencing self-care behavior of patients with diabetes in Chaiyaphum Province were expectation of diabetes control outcomes, social support from family, perceived diabetes severity, and social support from health team. These four variables together predicted self-care behavior of patients with diabetes by 46.3%. 2) The diabetes care model with community participation in Chaiyaphum Province was called the AFTER model, consisting of Assessment, Family support, Health Team support and Evaluation and Reflection. 3) After the implementation of the diabetes care model, It was found that the experimental group had knowledge about diabetes, perception of diabetes severity, perception of risk of diabetes complications, expectation of diabetes control results, expectation of diabetes control ability, social support for self-care in diabetic patients, and self-care behavior in diabetic patients which were significantly higher than before the experiment and the control group at a statistical significance level of .05.